Translation and Identity - Da Silva Matte, Neusa (Meta, 1996)
AbstractThe author presents part of her research on translation theory and poetry. Her approach is based on two assumptions: 1) that translation is a process which extrapolates textual dimension; 2) that this process Can be tackled from the perspective of (textual) identity.